The effect of postharvest ripening on strawberry bioactive composition and antioxidant potential - Goulas, Vlasios; Manganaris, George A. (My University, 2011)
Background: The aim of the present work was to evaluate the phytochemical profile and the antioxidant activity of strawberry fruit (cv. Camarosa) upon postharvest ripening at room temperature (20 °C) and to correlate them with qualitative attributes. Results: 'Camarosa' fruit retained an appreciable postharvest performance for up to 1 day shelf life; thereafter substantial quality deterioration was observed. An increased phenolic content, mainly attributed to hydroxycinnamic acids, flavonols and anthocyanins, was monitored after 3 days maintenance at 20 °C. The chromatographic fingerprint of athocyanins showed that pelargonidin-3-glucoside was the major anthocyanin, which increased with the increase of shelf life period, while cyanidin-3-glucoside and pelargonidin-3-rutinoside were found at lower concentrations. The potent radical scavenging activity, evaluated with four in vitro assays, showed a higher antioxidant capacity after 3 and 1 days of shelf life. In addition, the antioxidant effect of strawberry fruit extracts on lipid substrates and on an emulsion system showed a significant inhibition in the formation of conjugated diene hyperoxides. Interestingly, no direct correlation between the phytochemical profile and the quality attributes exist. Conclusion: 'Camarosa' fruit had acceptable quality attributes for fresh consumption and at the same time a high phytochemical content up to 1 day shelf life. The over-ripe fruit continued to be an excellent reservoir of natural antioxidants, pointing to its potential use as food antioxidant and nutritional supplement.
Keywords: Anthocyanins; Corn oil; Radical scavenging activity; Emulsion; Fragaria x ananassa; Liposomes; Phenolics